2021
DOI: 10.3389/fpls.2020.575462
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Transposable Elements and Satellite DNAs in Spinacia Species to Shed Light on Their Roles in Sex Chromosome Evolution

Abstract: Sex chromosome evolution has mostly been studied in species with heteromorphic sex chromosomes. The Spinacia genus serves as an ideal model for investigating evolutionary mechanisms underlying the transition from homomorphic to heteromorphic sex chromosomes. Among evolutionary factors, repetitive sequences play multiple roles in sex chromosome evolution while their forces have not been fully explored in Spinacia species. Here, we identified major repetitive sequence classes in male and female genomes of Spinac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 55 publications
(35 reference statements)
2
8
0
Order By: Relevance
“…Further previously described ‘satDNAs’ and minisatellites (i.e. Dione/ Fok I-satellite and Niobe/ Alu I-satellite: Zakrzewski et al 2010, 2014; BvMSats: Zakrzewski et al 2010; BvuSats: Li et al 2021) were not included as we found that these repeats are not arranged in long arrays and therefore we consider them tandem repeats rather than satDNA. The monomer sequences of newly identified satDNAs can be found in Additional file 1: Data S1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further previously described ‘satDNAs’ and minisatellites (i.e. Dione/ Fok I-satellite and Niobe/ Alu I-satellite: Zakrzewski et al 2010, 2014; BvMSats: Zakrzewski et al 2010; BvuSats: Li et al 2021) were not included as we found that these repeats are not arranged in long arrays and therefore we consider them tandem repeats rather than satDNA. The monomer sequences of newly identified satDNAs can be found in Additional file 1: Data S1.…”
Section: Resultsmentioning
confidence: 99%
“…76% in quinoa: Heitkam et al ., 2020; approx. 51% in spinach: Li et al ., 2021). Discrepancies in repeat abundances to a previous RepeatExplorer2 analysis in B. vulgaris (Kowar et al ., 2016) are moderate and result from the exclusion of organellar DNA from our read set as well as the improvement of the repeat annotation by including a more comprehensive, custom repeat database.…”
Section: Discussionmentioning
confidence: 99%
“…The similar results were presented in Spinacia oleracea L. (with homomorphic sex chromosomes) and S. tetrandra Stev. (with heteromorphic sex chromosomes) [56]. Li et al (2021) showed that the proportion of Ale and Retand was higher in the female genome than in the male genome, while the proportion of Angela, Bianca, CRM, Tekay, LINE, EnSpm_CACTA, and rDNA was higher in male genome than in the female genome of S. oleracea.…”
Section: Discussionmentioning
confidence: 99%
“…Then, FISH was performed as described previously by Li et al . (2021). The slides were observed and photographed under Olympus BX63 fluorescence microscope and then processed with P hotoshop v.7.0.…”
Section: Methodsmentioning
confidence: 99%
“…The PCR reaction procedure is as follows: denaturation at 95°C for 3 min; denaturation at 94°C for 25 s, annealing at 55°C for 30 s, and extension at 72°C for 40 s, 35 cycles; finally, extension at 72°C for 10 min. The mixed probe (STUYsdr‐1 and STUYsdr‐2) was labeled with Texas Red‐5‐dCTP, and 45S rDNA was labeled with Chroma Tide Alexa Fluor 488‐5‐dUTP using nick translation method (Li et al ., 2021) and stored at −20°C. The chromosome slides at metaphase, meiotic pachytene, diakinesis, metaphase I, and other stages were prepared.…”
Section: Methodsmentioning
confidence: 99%